Study of chemical bond strength of methyl methacrylate (MMA) based bonding agent on type I dentin collagen at various humidity - Adioro Soetojo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
One of the basic agents used in dentin bonding solution is methyl methacrylate (MMA). This bonding agent is widely used in dentistry. It have been proved that the adhesion between dentin bonding agent and collagen fibril is chemically bond; though the chemical bonding contribution is smaller than physical mechanical bond. The purpose of the research was to examined the chemical bonding strength of MMA based dentin bonding on type I dentin collagen at various humidity. Samples of treatment group were put into desiccator with 60%, 70%, 80%, and 90% humidity, while for control groups at room humidity (65%). Chemical bond of pure MMA and MMA mixed with collagen were measured by FTIR. The lower the value of MMA carbonyl, the higher absorbance band speak of chemical bond strength between MMA and collagen. Data was statistically analyzed with One-Way ANOVA at 95% confidence level continued with Tukey-HSD test. The result showed that the highest chemical bond strength was at 65% humidity (p ≤ 0.05). In conclusion, many esther carbonyl MMA molecules reacted with amino collagen at 65% humidity. This can be shown by the lowest peak's value of the MMA carbonyl absorbance at FTIR.